Influence of motivational factors on utilisation of Internet health information resources by resident doctors in Nigeria (2015)
This study aims to determine the influence of motivational factors: perceived ease of use (PEU), perceived enjoyment (PEJ) and perceived usefulness (PU) on utilisation of Internet health information resources among resident doctors in tertiary health-care institutions in Nigeria. The Internet has become a major source of health information for practitioners and the general public. Despite the availability of health information resources on the Internet, some resources are underutilised. There are numerous studies on Internet use among health-care workers; however, there is a dearth of information on motivational factors influencing utilisation of Internet health information resources among resident doctors in Nigeria. A descriptive survey design was used. Total enumeration technique was adopted to cover 1,280 resident doctors in 13 tertiary health-care institutions in southwestern Nigeria. A validated, self-administered questionnaire was used for data collection. The questionnaire has four sections covering the demographic profile of the respondents, PEU, PEJ and PU. Four hypotheses were tested at the p 0.0 1 level of significance. Data were analyzed using descriptive statistics, Pearson product-moment correlation and multiple regression analysis. There were more males (69.0 per cent) than females (31 per cent); respondents mean age was 34 years. The result revealed that PEU(r =0.181, p 0.01), PEJ(r = 0.166, p 0.01) and PU(r = 0.121, p 0.01) have significant relationship with utilisation of Internet health information resources by the respondents. Also, PEU, PEJ and PU collectively (F = 15.366, df = 3; 897, p <0.01) have significant influence on utilisation of Internet health information resources of the respondents. Individually, PEU (B = 0.864, df = 897, t = 3.90, p < 0.01) and PEJ (B = 0.349, df =897, t =3.060, p [lt]0.01) were found to have significant influence on utilisation while PU (B =0.232, df = 897, t = 1.328, p> 0.01) does not significantly influence the utilisation of Internet health information resource of the respondents. One major implication of this study is that system designers and web content developers should design programs and websites that are compatible with the user’s abilities. Medical librarians have a role to play in providing quality health content that is easy to navigate and pleasurable to use. Both the institutions and the government have a role to play in providing information and communication technology facilities to enable doctors access relevant health information resources easily. Practical implications – Introduction of information literacy training in the residency programme or inclusion as a component of the continuing professional development will enable resident doctors to know relevant online searching tools and search techniques for accessing health information resources which will be useful to their work. This will in turn increase their PU of Internet resources. Health sciences librarians (medical librarians) in the various institutions/centres have a role to play in training resident doctors on how to access, retrieve and evaluate online health information. Librarians should also train resident doctors on how to search evidence-based Medicine resources such as the Cochrane Library and PubMed Clinical Queries and Critical Appraisal of the medical literature to make informed decision in the management of their patients and for research purposes. They should be trained on how to organise bibliographic references using reference manager tools such as Endnote, Zotero or Mendeley. Social implications – The social implication of this findings is that systems that are easy to use should be designed, so that doctors will be able to access relevant information for research and patient care for better health outcomes. The easier and enjoyable the system is to use, the more resident doctors will access and use health information resources to improve their service and save more lives. Originality/value – This study examined three motivational factors (PEU, PEJ and PU) that influence the utilisation of Internet health information resources by resident doctors in tertiary health-care institutions in Nigeria. The result revealed that collectively PEU, PEJ and PU have significant relationship with the utilisation of Internet health information resources, but PEU and PEJ are the main drivers of use of Internet health information resources among the resident doctors studied. This study adds to the literature of motivational factors influencing utilisation of Internet health information resources by resident doctors in southwestern Nigeria. This paper is original because, to the best of our knowledge, there is no other study on motivational factors influencing Internet use among resident doctors in Nigeria.